A Contrastive Analysis between English Idioms and Their Indonesian Translations in the Novel The Girl on the Train by Paula Hawkins (2015) - Dian Novita Sari; Jumanto Jumanto (Universitas Dian Nuswantoro, 2018)
Abstract. This study explores to find out the similarities, the differences, and the learning problems in a particular context, through a contrastive analysis. The researchers have employed a descriptive, qualitative method during the research since the aim of this study is to find out the similarities, differences, and the learning problems of English idiom and its Indonesian translation in the novel The Girl on the Train by Paula Hawkins (2015). Based on the analysis that has been done, the researchers have found out that there are 16 verbal idioms, 6 informal idioms, 4 idioms with special keywords, 2 idioms related to special themes, and 2 idiomatic pairs. About the similarities and differences, the researchers have concluded that there are 13 of 16 English idioms similar to its Indonesian translations and 3 of them different. In the informal idiom-type, there are 3 English idioms similar to its Indonesian translations and also there are 3 English idioms different from its Indonesian translations. In the idioms with special-keyword type, there is no English idiom similar to its Indonesian translation, but there are 4 English idioms that are different from its Indonesian translations. In the idioms related to special-theme type, there are 2 English idioms similar to its Indonesian translations and there is no difference. In the idiomatic-pair type, there are 2 English idioms similar to its Indonesian translations, but there is no difference in this type. Indonesian learners should note these similarities and differences between English idiom and its Indonesian translation in the novel, so they will not face learning problems or make translating mistakes when translating idioms from English into Indonesian. This is essential, especially in a translation concerning the differences between the English and Indonesian idioms.Keywords: contrastive analysis, English and Indonesian idiom, idiom translation, Paula Hawkins’ The Girl on the Train Abstrak. Penelitian ini bertujuan menemukan persamaan dan perbedaan, serta masalah belajar dalam konteks tertentu, dengan metode analisis kontrastif. Penelitian ini bersifat kualitatif deskriptif, untuk menemukan persamaan, perbedaan, dan masalah belajar atau penerjemahan idiom dari bahasa Inggris ke dalam bahasa Indonesia dari novel The Girl on the Train karya Paula Hawkins (2015). Dari hasil analisis, ditemukan bahwa ada 16 verbal idioms, 6 informal idioms, 4 idioms with special keywords, 2 idioms related to special themes, dan 2 idiomatic pairs. Terkait dengan persamaan dan perbedaan, disimpulkan berdasarkan hasil penelitian bahwa ada 13 dari 16 idiom bahasa Inggris yang sama dengan terjemahan bahasa Indonesia, dan 3 idiom yang berbeda. Dalam tipe informal idiom, ada 3 idiom bahasa Inggris yang sama dengan terjemahan bahasa Indonesia, dan juga ada 3 idiom bahasa Inggris yang berbeda dari terjemahan bahasa Indonesia. Dalam tipe idioms with special keywords, idiom bahasa Inggris tidak ada yang sama dengan terjemahan bahasa Indonesia, tapi ada 4 idiom bahasa Inggris yang berbeda dari terjemahan bahasa Indonesia. Dalam tipe idioms related to special-theme type, ada 2 idiom bahasa Inggris yang sama dengan terjemahan bahasa Indonesia, namun tidak ada perbedaan. Dalam tipe idiomatic pair, ada 2 idiom bahasa Inggris yang sama dengan terjemahan bahasa Indonesia, namun tidak ada perbedaan. Pembelajar Indonesia harus mengenali persamaan dan perbedaan dari idiom bahasa Inggris dan terjemahan bahasa Indonesia yang ada di dalam novel, sehingga mereka tidak akan mengalami masalah belajar bahasa atau melakukan kesalahan penerjemahan ketika menerjemahkan idiom bahasa Inggris ke dalam bahasa Indonesia. Hal ini sangat penting, utamanya terkait dengan penerjemahan yang harus memperhatikan perbedaan yang ada antara idiom bahasa Inggris dan bahasa Indonesia. Kata kunci: analisis kontrastif, idiom bahasa Inggris dan Indonesia, penerjemahan idiom, The Girl on the Train Paula Hawkins